Effect of nanofluids in waste cooking oil biodiesel fuel: An experimental investigation on diesel engine characteristics. Issue 1 (October 2020) - Ramanathan, V; Jaikumar, M; Induja, S; SangeethKumar, E; SasiKumar, N
Abstract: The diminishing crude oil source and the environmental effluence created by the fossil fuels have forced the researchers to search for an alternative source of energy. Many researchers found that Waste cooking oil biodiesel (WCOB) derived from waste cooking oil (WCO) could be an economic source of fuel for diesel engines because some of the properties of WCOB were found similar to diesel. Disposing of WCO in sewage has been a great concern for many countries. Instead of disposing, converting WCO into WCOB, using them in diesel engines could be the best choice of utilizing energy. In this context, WCOB was selected as a basic fuel. In the first phase, experimentation was carried out using WCOB. Single-cylinder, water-cooled diesel engine with full set up was used for experimentation. Then, Zinc Oxide (ZnO) nanofluid was prepared by a wet chemical method in two mass proportions of 50ppm and 100ppm and blended with WCOB and considered fuels as WCOBZ50 and WCOBZ100. These fuels were tested and readings were measured. The experimental results showed that the engine characteristics were found better for WCOBZ100 compared to neat WCOB. In the second phase, ZnO with Copper Oxide (CuO) mixed nanofluid was prepared in two mass proportions of 50ppm and 100ppm and considered fuels as WCOBZC50 and WCOBZC100. Then these fuels were tested and results were evaluated with previous results. Finally, it was found that greater improvement in engine output characteristics and extreme drop in emission gases for WCOBZC100 compared to other nano blends and neat WCOB.